Physicochemical Properties of Crude and Purified of Glucomannan Flours - Heksa, Ayu Cahyarani; Rahmawati, Yeni; Nurkhamidah, Siti (IPTEK The Journal of Engineering, 2024)
Konjac glucomannan (KGM) is a versatile polysaccharide extracted from Amorphophallus species tubers. Commonly, extracted crude porang flour still has some impurities which limits the application of utilizing the material. High purity of processed glucomannan flour could satisfy the demand of growing awareness of healthy diet and industrial scale production. In this study, the physicochemical properties of purified glucomannan flour compared with crude porang flour were investigated. Thermal stability of the purified flour was increased indicated by higher degradation temperature, which was revealed by Thermogravimetric Analysis (TGA). The structural characteristics were investigated by FTIR and X-ray Diffraction (XRD) analysis. In addition, Scanning Electron Microscopy (SEM) was conducted to study the morphology and grain size of crude and purified flours. The results revealed that purified glucomannan flour has better thermal stability, higher crystallinity, smaller granule size and significantly higher viscosity compared to crude flour.